1962
DOI: 10.1109/tns2.1962.4315984
|View full text |Cite
|
Sign up to set email alerts
|

Photomultiplier Single-Electron Statistics

Abstract: SummaryLight Source Considerations to Secure Single PhotoelectronsOur measurements of the amplitude distribution of photomultiplier anode pulses due to the emission of single-electrons from the cathode consistently show a peak. It is significant that the peak position agrees with that of a calculated distribution based on a Poisson distribution of secondary electrons at each dynode. The integral distribution, obtained by counting single-electron pulses, tends to show a plateau. In low-light-level counting appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1963
1963
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…For all reasonable values of the dynode gains, P(n) shows a clear maximum, falling to zero at low pulse amplitudes. In practice, surprisingly good agreement with this simple theory is obtained with several types of photomultipliers (Brault and Gazier 1963a, b, Eberhardt 1964, Evrard and Gazier 1965, Fleishman 1962, Hyman et al 1964, Matheson 1964, Pertsev et al 1963, Pietri 1964, Tusting et al 1962. However, other workers (Baicker 1960, Baldwin and Friedman 1965, Barton et al 1964, Delany and Walton 1964, Prescott 1963, Rome 1964) have reported distributions that show no maximum, but fall monotonically with increasing pulse height.…”
Section: Introductionmentioning
confidence: 64%
“…For all reasonable values of the dynode gains, P(n) shows a clear maximum, falling to zero at low pulse amplitudes. In practice, surprisingly good agreement with this simple theory is obtained with several types of photomultipliers (Brault and Gazier 1963a, b, Eberhardt 1964, Evrard and Gazier 1965, Fleishman 1962, Hyman et al 1964, Matheson 1964, Pertsev et al 1963, Pietri 1964, Tusting et al 1962. However, other workers (Baicker 1960, Baldwin and Friedman 1965, Barton et al 1964, Delany and Walton 1964, Prescott 1963, Rome 1964) have reported distributions that show no maximum, but fall monotonically with increasing pulse height.…”
Section: Introductionmentioning
confidence: 64%
“…The authors remarked that their results were inconsistent with observed data, thus rejecting the hypothesis of the Poisson distribution P being a good descriptor for the PMT electron multiplication process. In spite of this conclusion, other authors [7][8][9] consistently reported measurements which did agree with the calculations by Lombard et al [6] and attribute the discrepant results of other work to noise in their experimental set-up [9]. Using an exponential distribution to describe the electron multiplication at the dynodes, Prescott et al [10] obtained good agreement between calculated and measured spectra for some specific types of PMT.…”
Section: Introductionmentioning
confidence: 89%
“…On the other hand, the Sb + CsO dynodes used by Tusting et al [9] consist of a more uniform thin layer of adsorbed material, which may account for a more constant g across the surface [11]. A possible conclusion from these evidences [12] is that one can assume that at each PMT stage the electron multiplication process follows indeed a Poisson distribution (P) given dynodes with uniform emission properties [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…hence, have undergone the full amplification of the PM tube have a pulse-height distribution closely approximated by a Poisson distribution (4. [18][19][20][21]. The integral pulse-height spectra for signal and dark pulses for a 1P28 photomultiplier tube are shown in Figure 2.…”
Section: Basic Considerations In Utilizing Photon Countingmentioning
confidence: 99%